2022
DOI: 10.1007/s00167-022-07237-3
|View full text |Cite
|
Sign up to set email alerts
|

Favorable long-term clinical and radiologic outcomes with high survivorship after autologous osteochondral transplantation of the talus

Abstract: Purpose To evaluate long-term clinical and radiologic outcomes of patients undergoing autologous osteochondral transplantation (AOT) for osteochondral lesions of the talus (OLT) and to perform a correlation analysis between clinical and radiologic outcomes. Methods Thirty-five patients with a mean age of 32.2 ± 8.9 years undergoing AOT for OLT between 1997 and 2003 were available for follow-up after an average of 19.1 ± 1.4 years. Demographic, surgical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Outcomes in 1 or more of these domains must reasonably be below the level of satisfaction in order for a patient to consider revision surgery. In contrast to arthroplasty studies, few studies to date have specifically focused on survival outcomes in joint preservation surgery for osteochondral lesions of the ankle 22,35,36 . This study sought to evaluate the long-term clinical survival after arthroscopic BMS for OLT and observed a high rate of survival that was sustained over time.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in 1 or more of these domains must reasonably be below the level of satisfaction in order for a patient to consider revision surgery. In contrast to arthroplasty studies, few studies to date have specifically focused on survival outcomes in joint preservation surgery for osteochondral lesions of the ankle 22,35,36 . This study sought to evaluate the long-term clinical survival after arthroscopic BMS for OLT and observed a high rate of survival that was sustained over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among the variety of surgical modalities, osteochondral transplantation is typically indicated for patients with large or cystic OLTs [21]. Previous studies have shown positive outcomes of autologous osteochondral transplantation (AOT) [2, 28, 30, 35]. In the setting of transplantation, intact articular cartilage harvested from the knee provides similar properties to hyaline cartilage for talar defects.…”
Section: Introductionmentioning
confidence: 99%